Synthesis of Fe0.32Co0.68/γ-Al2O3@C nanocomposite for depth treatment of dye sewage based on adsorption and advanced catalytic oxidation. Issue 14 (22nd March 2017) - Bao, Zepei; Ye, Lin; Fang, Beibei; Zhao, Lijun
Abstract : The Fe0.32 Co0.68 /γ-Al2 O3 @C nanocomposite can be utilized as a bifunctional adsorbent and catalyst for the degradation of organic dyes. Abstract : Herein, Fe0.32 Co0.68 binary metal nanoparticles synthesized at room-temperature were loaded onto a novel hierarchical flower-like γ-Al2 O3 @C composite, which improved the stability and dispersity of the Fe0.32 Co0.68 nanoparticles. The freshly prepared Fe0.32 Co0.68 /γ-Al2 O3 @C displayed good adsorption of Orange II (100 mg L −1, 973.55 mg g −1 ). Subsequently, the used Fe0.32 Co0.68 /γ-Al2 O3 @C adsorbent (Fe–Co oxide/γ-Al2 O3 @C) was reused as a peroxymonosulfate (PMS) catalyst. Amazing results were obtained, which demonstrated that Fe–Co oxide/γ-Al2 O3 @C can highly efficiently decompose Orange II (60 mg L −1, 1 min; 90 mg L −1, 2 min, 120 mg L −1, 7 min and 150 mg L −1, 10 min) as a PMS catalyst. It also exhibited good general degradation of different organic pollutants and excellent reusability (98%, tenth cycle) due to the structural stabilities of γ-Al2 O3 @C. Further, an experiment was carried out to treat high concentrations of Orange II (200 mg L −1 ) with the Fe0.32 Co0.68 /γ-Al2 O3 @C nanocomposite. After adsorption, PMS was added, and 98% degradation occurred within 5 minutes. The combination of adsorption and PMS advanced oxidation techniques may be one of the effective ways to deal with high-concentration dye wastewater.